2011
DOI: 10.3390/molecules161210433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginkgo Leaf Parenteral Solution on Blood and Cochlea Antioxidant and Immunity Indexes in OM Rats

Abstract: Oxidative stress is involved in the development and progression of otitis media (OM). In this study, we investigated the effect of Ginkgo leaf parenteral solution on blood and cochlea antioxidant and immunity indexs in OM rats. In OM model rats, blood and cochlea malondialdehyde (MDA), nitric oxide (NO), tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8) and interleukin-10 (IL-10) levels were significantly increased, whereas antioxidant enzymes activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In this study, rams in G60 and G100 groups had a considerably higher IgA, IgG and IgM values compared to those in the G0 group, which might due to the phenolic compounds and flavonoids in the bark and leaves of B. papyrifera, which apparently are the main components responsible for the antioxidant activity (Du et al 2008;Kai et al 2015). Previous studies have shown that plant flavonoids are a predominant class of plant secondary metabolites with immunity-boosting activities (Middleton 1998;Proestos et al 2006;Zhao et al 2011), they can extend the activity of vitamin C, act as antioxidants, and may, therefore, enhance immune functions (Acamovic and Brooker 2005). Si et al (2018) also observed an increase in IgA, IgG and IgM in the serum of dairy cows with the addition of B. papyrifera silage (Si et al 2018).…”
Section: Discussionmentioning
confidence: 92%
“…In this study, rams in G60 and G100 groups had a considerably higher IgA, IgG and IgM values compared to those in the G0 group, which might due to the phenolic compounds and flavonoids in the bark and leaves of B. papyrifera, which apparently are the main components responsible for the antioxidant activity (Du et al 2008;Kai et al 2015). Previous studies have shown that plant flavonoids are a predominant class of plant secondary metabolites with immunity-boosting activities (Middleton 1998;Proestos et al 2006;Zhao et al 2011), they can extend the activity of vitamin C, act as antioxidants, and may, therefore, enhance immune functions (Acamovic and Brooker 2005). Si et al (2018) also observed an increase in IgA, IgG and IgM in the serum of dairy cows with the addition of B. papyrifera silage (Si et al 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Biological systems have protective arrangements which defend them against the harmful effects of free radicals. This includes SOD and CAT [22]. In the liver tissues of the hepatotoxicity control group, the antioxidant activity of SOD and CAT were significantly ( p < 0.001) reduced as compared with the normal animal group.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that the active compounds of flavones and terpenes in GBL have immune enhancing activities that include promotion of lymphocyte synthesis, cytokine release, immunoglobulin levels and phagocytosis activity (Zhao et al . ). In the present study, diets supplemented with FGBLR enhanced both humoral and cellular immunity of piglets.…”
Section: Discussionmentioning
confidence: 97%